Multi-omics analysis of gut microbiota and metabolites reveals the effects of rearing systems on the duodenum and cecum gut barriers of lueyang black-bone chickens - Shao, Linqing; Zhao, Mingming; Zeng, Shuang; Wang, Ling; Wang, Shanshan; Zeng, Wenxian; Lu, Hongzhao (Frontiers in Microbiology, 2025)
IntroductionGut health is a critical determinant of poultry growth, immunity, and meat quality, with the intestinal barrier being fundamental to its maintenance. This study aimed to investigate the impacts of caged and cage-free rearing systems on the gut barrier of Lueyang black-bone chickens, specifically focusing on how these systems alter gut microbiota composition and metabolic profiles.MethodsLueyang black-bone chickens were raised under either caged or cage-free conditions. Gut barrier integrity was assessed through histological examination of the duodenum and cecum. Microbial community structure was analyzed via 16S rRNA sequencing, and metabolic changes were profiled using LC–MS-based non-targeted metabolomics.ResultsHistological analysis revealed significantly greater intestinal wall thickness and higher goblet cell counts in the cage-free group (p < 0.0001). Microbiome sequencing showed that the caged group was enriched with fiber-degrading bacteria such as Bacteroides and Rikenellaceae_RC9_gut_group, while the cage-free group had a higher abundance of potential pathogens like Acinetobacter and Campylobacter. Metabolomics results indicated upregulation of bile acids and unsaturated fatty acids in the caged group, whereas phosphatidylcholine (PE) and lysophosphatidylcholine (LPC) were significantly elevated in the cage-free group. Further integrated analysis revealed strong positive correlations between Rikenellaceae_RC9_gut_group and bile acids, and between Odoribacter/Clostridia_UCG-014 and unsaturated fatty acids including traumatic acid.DiscussionThe findings suggest that caged rearing promoted a more beneficial microbial community structure, characterized by fiber-degrading bacteria that subsequently elevated anti-inflammatory and barrier-strengthening metabolites such as bile acids and unsaturated fatty acids. In contrast, the cage-free environment may predispose chickens to potential gut inflammation and barrier dysfunction, partly linked to higher levels of harmful bacteria and membrane phospholipid metabolites. These results highlight the role of rearing systems in modulating gut health through microbiota-metabolite interactions.